2006
DOI: 10.1111/j.1540-5907.2006.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

Value Choices and American Public Opinion

Abstract: Special thanks go to George Rabinowitz and Saundra K. Schneider; this project could not have been completed without their assistance. I would also like to thank Paul Sniderman for making me a part of the 1994 Multi-Investigator Study and for his continued interest in, and support of, this research. I appreciate very much the excellent comments and suggestions that were provided by Stanley Feldman, John Geer, George Marcus, Michael Martinez, David Peterson, Gregory Pettis, David Redlawsk, Darren Schreiber, Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
143
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(152 citation statements)
references
References 35 publications
6
143
0
3
Order By: Relevance
“…These panels were already used successfully in a number of studies in the areas of health and medicine, political and social sciences, and economics and public policy. [77][78][79][80][81] Methodological studies have shown that data from such panels are comparable to the results obtained through traditional probabilistic surveys.…”
Section: Methods Samplementioning
confidence: 90%
“…These panels were already used successfully in a number of studies in the areas of health and medicine, political and social sciences, and economics and public policy. [77][78][79][80][81] Methodological studies have shown that data from such panels are comparable to the results obtained through traditional probabilistic surveys.…”
Section: Methods Samplementioning
confidence: 90%
“…4 There is an extensive and important body of work examining the relationship between a variety of political attitudes and other characteristic adaptations. These adaptations include, among others, RWA (e.g., Adorno et al 1950;Altemeyer 1996;Ekehammar et al 2004;Feldman 2003;Feldman and Stenner 1997;Hetherington and Weiler 2009;Stenner 2005), SDO (e.g., Ekehammar et al 2004;Sidanius and Pratto 1999;Sidanius, Pratto, and Bobo 1996), Racial Resentment (e.g., Feldman and Huddy 2005;Henry and Sears 2002;Kinder and Mendelberg 2000;Kinder and Sanders 1996;Kinder and Sears 1981;Sniderman and Carmines 1997), and core values (e.g., Goren 2001Goren , 2005Jacoby 2006). Our work contributes to this research by examining (1) how basic dispositional traits-arguably formed prior to these characteristic adaptations-shape political attitudes (another characteristic adaptation) and (2) how the effects of Big Five traits vary across clearly identified contexts.…”
Section: Dispositional Traits-the Big Fivementioning
confidence: 99%
“…One is built around the idea that citizens select candidates and parties that are closest to their own preferences. After all, citizens have stable predispositions such as values that influence political issue positions [21] and vote choice [22]. Since politicians want to get elected or stay in office, they adjust their positions according to the will of the public [23].…”
Section: Elite Influence Explanations and Endogeneitymentioning
confidence: 99%